Revision of the Scopula dubernardi species group: how many species? (Lepidoptera: Geometridae, Sterrhinae) - Sihvonen, Pasi; Stüning, Dieter (Zootaxa, 2006)
The Palaearctic Scopula dubernardi species group (Lepidoptera: Geometridae) is revised on the basis of external and genitalic characters to include Scopula dubernardi (Oberthür, 1923) and Scopula segregata Prout, 1919. Lectotypes are designated for both species, which were described from more than one specimen without holotype designation. The species delimitation is based on small quantitative differences in the female genitalia, i.e., the degree of turn of the ductus bursae along its axis, and on external features. Furthermore, the recognition of the studied taxa as separate species is strengthened by the observation that they occur sympatrically and synchronously in two localities. Unlike the common situation in the genus Scopula, structures of the male genitalia were found uninformative in species delimitation. The length of right ceras on the 8th sternite of S. segregata was found to be polymorphic. Adults and genitalia of S. dubernardi and S. segregata are illustrated, along with the variation in external features and genitalia in both species. The biology and immature stages of both species are unknown.